Application of venovenous extracorporeal membrane oxygenation combined with continuous renal replacement therapy in a high-risk liver transplant recipient: a case report - Yang, Li Wen; Zhang, Yunli; Lu, Lijun; Xiong, Bin (Frontiers in Transplantation, 2025)
IntroductionThis report describes the novel perioperative application of VV-ECMO combined with CRRT in a high-risk liver transplant recipient with irreversible hypoxemia and multi-organ dysfunction, expanding therapeutic options for traditionally contraindicated patients.Case presentationA 27-year-old male with acute-on-chronic liver failure (chronic hepatitis B + alcoholic liver disease), hepatic encephalopathy, severe pulmonary infection, and coagulopathy developed life-threatening hypoxemia (PaO2 60 mmHg on FiO2 100%) during transplantation.InterventionsEmergency intraoperative VV-ECMO and postoperative CRRT were initiated.OutcomesECMO was withdrawn on postoperative day 4, the ventilator on day 11, and the patient was discharged on day 61. Follow-up showed normal liver function.ConclusionCombined VV-ECMO/CRRT provides synergistic cardiopulmonary-renal support for high-risk liver transplants, creating a critical window for graft recovery. Multidisciplinary coordination is essential for success.